PENGARUH SUBSITUSI PUPUK ORGANIK TERHADAP PUPUK ANORGANIK PADA PERTUMBUHAN DAN HASIL BAWANG MERAH (Allium ascalonicum. L) - DAMUD DAMUD; Teguh Supriyadi; MAHANANTO MAHANANTO (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2011)
This research with objective to know the best effect substitution of organic manure and in anorganic fertilizers on the growth and yield of shallot was conduted on Augustus-September 2009 in the Village Sengon, sub district, Brebes, Central Java. 75 meters above level with vertisol soil. The field experiment was used one factor with five treatment arranged in Â Randomizyd Complete Block Design (RCBD) with five replication. The treatment were A; 100% inorganic fertilizer + organic fertilizer, B: 75% inorganic fertilizer + organic fertilizer, C, 50% inorganic fertilizer + organic fertilizer, D; 25% inorganic fertilizer + organic fertilizer, E; 0% inorganic fertilizer + organic fertilizer. The result showed inorganic fertilizer + substitution organic fertilizer of provide efficient use of inorganic fertilizers. The highest yield of onion resulted treatment A: 100% fertilizer inorganic+substitution fertilizer organic is 5.080 g (21,15 ton/ha). The lowest yield of onion resulted by treatment E: 0% inorganic+organic fertilizer 150 kg/ha is 3.450 g (14,78 ton/ha).